Turgor Pressure Sensing in Plant Cell Membranes - Coster, Hans G. L. (1976)
Experimental evidence is reviewed which shows that the cell membrane is compressible by both mechanical and electrical forces. Calculations are given which show that significant changes in the thickness of cell membranes can occur as a result of (a) direct compression due to the turgor pressure; (b) indirect effects due to the stretching of the cell wall; and (c) the stresses induced by the electric field in the membrane. Such changes in the membrane thickness may provide the pressure-transducing mechanism required for osmoregulation and growth. An important feature of the model is that this pressure transduction can occur not only in the plasmalemma (where there is a pressure gradient), but also in the tonoplast.